Association between gut microbial diversity and technique failure in peritoneal dialysis patients - Shulan Guo; Huan Wu; Ji Ji; Zhaoxing Sun; Bo Xiang; Weiwei Wu; Jun Ji; Jie Teng; Xiaoqiang Ding; Xiaofang Yu (Renal Failure)
Background Gut dysbiosis in peritoneal dialysis (PD) patients causes chronic inflammation and metabolic disorders which result in a series of complications, probably playing an important role in PD technique failure. The reduction in gut microbial diversity was a common feature of gut dysbiosis. The objective was to explore the relationship between gut microbial diversity and technique failure in PD patients.Methods The gut microbiota was analyzed by 16s ribosomal RNA gene amplicon sequencing. Cox proportional hazards models were used to identify association between gut microbial diversity and technique failure in PD patients.Results In this study, a total of 101 PD patients were enrolled. During a median follow-up of 38 months, we found that lower diversity was independently associated with a higher risk of technique failure (hazard ratio [HR], 2.682; 95% confidence interval [CI], 1.319–5.456; p = 0.006). In addition, older age (HR, 1.034; 95% CI, 1.005–1.063; p = 0.020) and the history of diabetes (HR, 5.547; 95% CI, 2.218–13.876; p < 0.001) were also independent predictors for technique failure of PD patients. The prediction model constructed on the basis of three independent risk factors above performed well in predicting technique failure at 36 and 48 months (36 months: area under the curve [AUC] = 0.861; 95% CI, 0.836–0.886; 48 months: AUC = 0.815; 95% CI, 0.774–0.857).Conclusion Gut microbial diversity was independently correlated with technique failure in PD patients, and some specific microbial taxa may serve as a potential therapeutic target for decreasing PD technique failure.